Patriarchal Regime of the Spectacle: Racial and Gendered Gaze in Jhumpa Lahiri’s Fiction - Moussa, Pourya Asl; Abdullah, Nurul Farhana Low (Australian International Academic Centre (AIAC), 2017)
This article attempts to evince the political, cultural and affective consequences of Jhumpa Lahiri’s diasporic writings and their particular enunciations of the literary gaze. To do so, it details the manner in which the stories’ exercise of visual operations rigidly corresponds with those of the Panopticon. The essay argues that Lahiri’s narrative produces a kind of panoptic machine that underpins the ‘modes of social regulation and control’ that Foucault has explained as disciplinary technologies. By situating Lahiri’s stories, “A Real Durwan” and “Only Goodness,” within a historicalpolitical context, this essay aims at identifying the way in which panopticism defines her fiction as both a record of and a participant in the social, sexual and political ‘paranoia’ behind the propaganda of America’s self-image as the land of freedom. We maintain that Lahiri’s fiction situates itself in complex relation to the postcolonial concerns of the late twentieth century, suggesting that through their fascination with a visual literalization of the panoptic machine, and by privileging the masculine gaze, the stories legitimate the perpetuation of socially prescribed notion of sexual difference.